Truck appointment systems: How can they be improved and what are their limits? - Ann-Kathrin Lange; Nicole Nellen; Carlos Jahn (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Rising handling volumes and increasingly profound disruptions of global transport chains are placing severe stresses on container terminal processes. This affects landside handling in particular. In order to relieve this burden, more and more truck appointment systems have been introduced over the past 20 years, but they have only partially fulfilled the hopes placed in them. This study identifies the potential for improvement but also shows the limitations of this approach. Methodology: In order to highlight the different approaches used both in academia and in practice to adapt truck appointment systems to the respective requirements and to arm them against disruptions, a structured literature review was conducted. A total of 136 scientific publications were classified and the results were evaluated in detail. Findings: The developed solution approaches often only refer to individual sub-problems of container terminals instead of including the entire terminal or even the entire port with all its stakeholders. Furthermore, combinations of different methods are rarely used, where the weaknesses of individual methods could be compensated. Originality: The massive disruption of the global transportation chain has created new challenges for truck appointment systems. A structured analysis of the possibilities and limits has not yet taken place from this point of view.
urn:nbn:de:gbv:830-882.0200785; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Port Logistics